Risk preferences under extreme poverty : a field experiment (2010)
Until now, the dominant belief concerning the relationship between poverty and risk aversion is that the poor are more risk averse. If the poor are more risk averse, then they will choose "low risk-low return" activities that trap them in poverty. However, both empirical and experimental evidence show no clear pattern such as would suggest that the poor are somehowmore averse to risk than others; at times, they even seem to embrace risk, while at other times, there seems to be no difference. Focus has tended to be on extreme behaviors, as these are related to sub-optimal decisions such as have even raised questions whether an individual can be simultaneously both poor and rational. Amongst all the available empirical evidence, there is one bit of evidence of special interest-changes in behavior whenever subsistence is at risk. This paper emerges from the fact that recent experimental evidence in both psychology and economics suggests that certain decisions made under risk respond to reference points.We develop a theory within the traditional streamof rational choices, whereby the references are set by only observable variables, such as prices and family size...